Preface: 7th International Conference on Computer Engineering, Information Science & Application Technology (ICCIA 2024) - Ma, Zhenliang; Kam, Fanny (Transactions on Computer Science and Intelligent Systems Research, 2024)
The organizing Committee of ICCIA 2024 was proud to present the proceedings of the 7th International Conference on Computer Engineering, Information Science & Application Technology (ICCIA 2024), held on May 18-19, 2024 in Hong Kong, China. The aim of ICCIA 2024 is to provide a platform for researchers, engineers, academicians, as well as industrial professionals, to present their research results and development activities in computer engineering, information science, application technology. It provides opportunities for the delegates to exchange new ideas and application experiences, to establish business or research relations and to find global partners for future collaboration. We hope that the conference results will lead to significant contributions to the knowledge in these up-to-date scientific fields. This two-day conference is being organized in technical association with Asian Union of Information Technology, Research Center of Engineering and Science, and will include invited keynote talks and oral paper presentations from both academia and industry to ignite our young minds, to initiate them in the field of meaningful research and thereby enrich their existing knowledge. By submitting a paper to this 7th ICCIA, the authors agree to the review process and understand that papers undergo a peer-review process. Manuscripts will be reviewed by appropriately qualified experts in the field selected by the Conference Committee, who will give detailed comments and-if the submission gets accepted-the authors submit a revised version that takes into account this feedback. All papers are reviewed using a double-blind review process: authors declare their names and affiliations in the manuscript for the reviewers to see, but reviewers do not know each other’s identities, nor do the authors receive information about who has reviewed their manuscript. The Committees of the 7th ICCIA invest great efforts in reviewing the papers submitted to the conference and organizing the sessions to enable the participants to gain maximum benefit. Hopefully, all participants and other interested readers benefit scientifically from the proceedings and also find it stimulating in the process. With our warmest regards, Zhenliang Ma, Fanny Kam Conference Organizing Committee